Using Clinically Based Vignettes to Further Develop a Mass Gathering Triage Tool. Issue Volume 34:Issue s1(2019) (May 2019) - Ranse, Jamie; Cannon, Matt; Roitman, Rebecca; Morphet, Julia
Abstract : Introduction: This research builds on a previously developed triage: Mass Gathering Triage Scale (MaGaTT) by Cannon, et al (2017). This tool was targeted towards non-health care professional first responders within mass-gathering events (MGEs). However, this tool had not been evaluated. Aim: To further develop the previously designed MaGaTT using vignettes of clinical cases to: 1) determine variation in decision-making, and 2) inform further tool development prior to real-world testing. Methods: Volunteer members of St. John Ambulance Australia were surveyed using 18 vignettes of de-identified real patient record forms from MGEs covered by St. John Ambulance Australia (NSW) in 2013-2014. Participants were given the MaGaTT and written instructions on its use. Participants triaged 18 patients, recording their decisions on the online survey. Responses against the vignettes were analyzed using Fleiss Kappa [p-bar] measure. A score of 0.61 – 0.8 represented substantial agreement and a score of between 0.41 and 0.6 represented moderate agreement between participants. Results: There were 110 completed responses. The majority of participants were male (n =66, 60%), having completed a Bachelor's Degree (n =38, 34.5%), and holding the clinical skill level of "first responder" (n=42, 38.2%). The overall agreement [p-bar] for the 18 items was moderate at 0.55. When examined by triage category, the "Resuscitation" category had substantial agreement (0.69), when compared with moderate agreement for "Urgent" (0.52) and "Minor" (0.52) categories. Discussion: This research demonstrates that the MaGaTT can be used with moderate agreement, and substantial agreement within the resuscitation category. This is similar to triage tools internationally, where high levels of agreement relate to triage categories for patients requiring resuscitation when compared to patients requiring lower levels of clinical care. Slight changes have been made to the original MaGaTT as a result of this research.